PENGETAHUAN REMAJA USIA 15-17 TAHUN DI SMAN 4 KOTA BANDA ACEHTERHADAP EFEK SAMPING PEMAKAIAN ALAT ORTODONTI CEKAT - Herwanda Herwanda; Rafinus Arifin; Lindawati Lindawati (Journal of Syiah Kuala Dentistry Society, 2016)
The purpose of orthodontic appliance is now more widely used by teenagers. Most teenagers using orthodontic tool for lifestyle, without knowing and not considering the main purpose, benefits and risks of orthodontic treatment. The purpose of thisstudy was to determine the level of knowledge of teenagers age 15-17 years in SMAN 4 Banda Aceh to the side effects of using fixed orthodontic appliance. Design of study was descriptive. The number of subjects in this study were 96 people, subjects retrieved using non-probability sampling and purposive sampling technique. The results of the study showed 25 subjects (26%) have knowledge in the high category, 68 subjects (70.9 %) have knowledge in the medium category, and 3 subjects (3.1 %) have knowledge in the low category. The conclusion in this study is that knowledge of students in SMAN 4 Banda Aceh on the side effects of fixed orthodontic appliance use are in the medium category.Keywords : Knowledge, fixed orthodontic, side effect